Building teacher identity: reflections with young professionals - Orozco Castro, Cynthia (2025)
In the educating and learning process at any educational level, teaching is a complex activity. Throughout this process, skills in the art of teaching are acquired and refined, gradually forming a sense of self. Professional identity is not acquired simply by obtaining a degree, which allows one to practice the profession, but rather constitutes a process of acquiring greater expertise, as well as individual and collective growth. This article reflects on learnings and insights derived from the course: Personal and Professional Development of Educators, which is a new theoretical-practical proposal at the undergraduate level for the fields of Early Childhood Education and Primary Education with a concentration in English. The main objectives are to review the construction of professional identity, problematize the conditions that hinder personal and professional growth, and promote self-care practices in teaching. This work explores the process of 31 young professionals who have been working for a few years: 14 in Early Childhood Education and 17 in Primary Education, during the first semester of 2024 at the Western Campus of the University of Costa Rica.  Through the construction of metaphors, it explores the idealization surrounding the teaching profession. Additionally, it analyzes the challenges present in the daily educational practice by examining self-records of the educators, analyzing triggers, emotions, thoughts, and reactions of intersubjectivity and subjectivity in their classroom experiences. This article highlights the weight of historically constructed representations in the collective imagination about the ideal of teaching, which contrasts with the challenges of the current context and everyday experiences, offering some proposals centered on collective care.